The extent of continental material in oceans: C-Blocks and the Laxmi Basin example. Issue 3 (5th May 2020) - Geoffroy, L; Guan, H; Gernigon, L; Foulger, G R; Werner, P
SUMMARY: We propose a tectonic interpretation for the outer-SDRs (SDRs: Seaward-Dipping Reflectors) and Pannikar central ridge in the aborted Laxmi Basin west of India from wide-angle seismic reflection data. The outer-SDRs comprise syn-tectonic extrusives (lavas and/or volcaniclastics) emplaced above passively exhumed mid-to-lower mafic crust of continental origin. They erupted following sudden lithosphere weakening associated with isolation of a continental block (a 'C-Block'). Continuous magmatic addition during crustal extension allowed stretching of the lower crust whilst maintaining constant or even increasing thickness. A similar process occurred at both conjugate margins allowing bulk, pure-shear plate separation and formation of linear magnetic anomalies. The Laxmi example can explain enigmatic features observed in mature oceans such as presence of distal buoyant plateaus of thick continental crust away from the margins.